Surgical treatment of a floating non-occlusive thrombus in the ascending aorta: case report - Ribeiro,Paulo José de Freitas (2003)
We report the case of a 44-year-old diabetic woman who was a smoker using synthetic progestagen, with previous history of suspected thrombotic cerebral ischemia. She was admitted with clinical evidence of acute myocardial infarction. A coronary angiogram showed normal coronary arteries and distal occlusion of the left circumflex coronary artery. An ascending aorta angiogram and transesophageal echocardiography revealed a free floating mass attached to the aortic wall. The pedunculated thrombotic mass was surgically removed. Histological examination of the resected structure confirmed the macroscopic findings and revealed a recent thrombus. The patient was prescribed oral anticoagulant and released from hospital.